Fundraising Management Optimalization of Zakat Infaq and Alms in The Countryside - Hendri Hermawan Adinugraha (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
The purpose of this study is to find out how to optimize the ZIS (Zakat, Infaq and Shadaqah(alms)) fundraising through rural community activities. The research location is located inMergolangu village, Wonosobo District. This research uses an analytical descriptive approach ofqualitative and is equipped with relevant literature sources. Data analysis techniques using Milesand Huberman interactive model. The results of this study indicate that the management of ZISfundraising through community activities in Mergolangu Village is quite effective, this can happenbecause it still maintains the customs and traditions in the village that are always oriented to theharmony of citizens and local wisdom. So that the residents are still very enthusiastic in followingthe social activities in rural areas coupled with the activities of accumulating ZIS funds, althoughwith the nominal relatively not too much but because of the regular activities of the ZIS funds arealso collected a lot. The distribution system uses the principle of “from citizens, by citizens, and forcitizens” as a manifestation of the icon “gotong-royong” typical of Indonesia